Influence of Twin Carbide Structure on Friction and Wear Properties of G95Cr18 Stainless Bearing Steel - Guo, Hao; Du, Sanming; Lei, Jianzhong; Zhang, Yongzhen; Hu, Linzhuang (Frontiers in Materials, 2019)
G95Cr18 stainless bearing steel is used to manufacture rolling bearings widely used in aviation and navigation fields. Twin carbide structure often appears in G95Cr18 stainless bearing steel structure and affects its material properties. This study adopts ball-block friction pairs to qualitatively discuss the influence of twin carbide structure of different degrees on the friction and wear performance of G95Cr18 stainless bearing steel under dry sliding conditions at room temperature and atmospheric environment. The results show that a slight twin carbide structure has only a little influence on the friction coefficient but can reduce the wear rate slightly, while a severe twin carbide structure can significantly increase the friction coefficient and wear rate. Thus, the existence of an optimal value for twin carbide structure was confirmed. The wear mechanism is mainly oxidation wear and abrasive wear, and the oxide produced by oxidation reaction during friction consists mainly of Fe2O3.